Bacterial Vaginosis and Sexually Transmitted Infections in an HIV-Positive Cohort - Nava-Memije, Karina; Hernández-Cortez, Cecilia; Ruiz-González, Verónica; Saldaña-Juárez, Claudia A.; Medina-Islas, Yazmín; Dueñas-Domínguez, Roberto A.; Aguilera-Arreola, Ma. Guadalupe (Frontiers in Reproductive Health, 2021)
The World Health Organization (WHO) and the Joint United Nations Programme on HIV and AIDS (UNAIDS) suggest that sexually transmitted infection (STI) surveillance should include other genital infections and not only human immunodeficiency virus (HIV). To monitor the concomitance of bacterial vaginosis (BV) and STIs in HIV-seropositive (HIV+) and HIV-seronegative (HIV–) patients, a prospective study was conducted in a cohort of 349 volunteers at a clinic specializing in treating STIs in Mexico City. Microbiological and molecular methods were used to detect STIs and dysbiosis in HIV+ and HIV– individuals. The prevalence of infection was higher in HIV+ (69.28%) than in HIV– (54.87%) individuals. BV was the most frequent infection in HIV+ individuals, and polymicrobial infections were 3 times more common in HIV+ individuals than in HIV– individuals (31.48 vs. 10.98%). Behaviors documented in a self-administered questionnaire included low condom use frequency in HIV+ individuals co-infected with BV or a STI. This finding highlights the importance of surveillance using routine microbiological evaluations for the correct management of genital infections in HIV+ patients because in the presence of HIV, the clinical presentations, courses, and therapeutic responses of some STIs can differ from those in patients without HIV infection.